Історичний дискурс гедонізму у контексті новітніх електронних ЗМІ - Косюк, Оксана Михайлівна; Kosiuk, O. M. (Львівський національний університет імені Івана Франка, 2003)
Подано аналіз та класифікацю розважальної продукції електронних ЗМІ (за вертепною традицією). The article deals with analysis and classification of entertaining production elektronic mass media (according to tne Nativity Play tradition).
Entertaainments producted by elektronik mass media as transitive phenomena in history of culture
Keywords: розвага; гра; видовище; гедонізм; гедонізм; entertainment; play; spectacle; hedonism; nativity play